Onset of circadian rhythmicity in the brain of Atlantic salmon is linked to exogenous feeding. - Mariann Eilertsen; Sissel Norland; David W P Dolan; Rita Karlsen; Ana S Gomes; Charlotte M Bolton; Herve Migaud; Ivar Rønnestad; Jon Vidar Helvik (PLoS ONE)
An organism's biological processes are adapted to and driven by rhythmicity in the natural environment and periodicity of light is one of the most influential factors. In a developing organism, the onset of circadian rhythmicity might indicate the time point of functional necessity for aligning processes to the environment. Here, the circadian clock mechanism has been studied in the developing brain of Atlantic salmon (Salmo salar), by comparing the endogenous feeding alevin, independent on the environment for nutritional supply, to the exogenous feeding fry, dependent on the light period for detecting and catching prey. The results showed that while only a few clock genes were cyclic in the yolk sac alevins, many of the clock genes and genes of the circadian rhythm pathway cycled significantly in the feeding fry. Few genes were differentially expressed between time points in the circadian sampling series during the yolk sac stage, but several hundred genes were found differentially expressed in the first feeding stage. Genes important for cell cycle progression were cyclic or differentially expressed between time points after exogenous feeding, indicating a clock-controlled cell cycle at this stage. The expression of important genes in the melatonin synthesis were also cyclic in the feeding fry with an acrophase in the transition between light and dark or in darkness. Analyzing the impact of exogenous feeding on the developing brain supported a shift from utilization of proteins and lipids in the yolk to utilization and allocation of dietary energy and nutrients. Taken together, the life history transition related to onset of exogenous feeding is linked to the establishment of a persistent circadian rhythmicity in the salmon brain, which needs to be synchronized to light-dark cycles to enable the fry to search and capture feed.